Effect of Cobalt-hydroxybenzoate Complex on Genomic DNA - KADIR DEVRIM, A.; ARSLANTAS, ALI; KAYA, NECATI; NECEFOGLU, HACALI (Asian Journal of Chemistry, 2010)
In this study, the interaction between [Co(H2O)6] (p-HOC6H4COO)2·2H2O complex and genomic DNA were investigated. DNA samples have been isolated from cattle leucocytes and the investigation carried out by incubating samples with the complex at 37ºC. The effect of the metal complex on genomic DNA was ascertained by agarose gel electrophoresis at 50 V for 2 h. The intensity of the bands on the gel depends on the concentrations of the complex. The mobility of the bands decreased as the concentration of complex increased, indicating the occurrence of increased covalent binding of the metal complex with DNA. The damage effect of the added ascorbate into the medium might be depend on the free radicals produced from oxidation of ascorbate by molecular oxygen and this damage was reduced by the metal complex.